Thoracoabdominal breathing pattern across exercise intensity domains: performance level insights in cyclists - de Castro Lopes, A. L.; Rodrigues, I. M.; Bernardina, G. R. D.; de Barros Sousa, F. A.; de Almeida Rodrigues, N.; Massaroni, C.; Schena, E.; Silvestri, S.; Cerveri, P.; Silvatti, A. P. (Sports Biomechanics, 2025)
Thoracoabdominal breathing pattern (THA) can be influenced by factors such as exercise intensity, postural demands, and individual variability, which could be associated with performance level. The present study aims to investigate the THA of cyclists with different performance levels during increasing exercise intensity. Fourteen male professional cyclists performed resting breathing manoeuvres and a step-incremental test on a cycle ergometer. Physiological responses were monitored using a metabolic gas analyser and were then classified into two groups: Higher and Lower VO2max. THA was recorded with an optoelectronic system. The contribution to tidal volume and the coordination of three compartments, namely superior thorax (ST), inferior thorax (IT), and abdomen (AB), were calculated. Higher VO2max group demonstrated a stable contribution across all intensity thresholds. Lower VO2max group increased the AB contribution by approximately 9% at both ventilatory thresholds from the start, while the rib cage contribution (ST + IT) decreased by approximately 17% from quiet breathing to exercise (p < 0.005). Coordination between ST vs. AB and IT vs. AB showed significant differences, with the Lower VO2max group demonstrating lower values and a greater effect size compared to the Higher VO2max group (p < 0.005). The present study provides valuable insights into how athletes of different performance levels employ distinct patterns of THA.